Anti-Book - Thoburn, Nicholas (University of Minnesota Press, 2023)
No, Anti-Book is not a book about books. Not exactly. And yet it is a must for anyone interested in the future of the book. Presenting what he terms "a communism of textual matter," Nicholas Thoburn explores the encounter between political thought and experimental writing and publishing, shifting the politics of text from an exclusive concern with content and meaning to the media forms and social relations by which text is produced and consumed. Taking a "post-digital" approach in considering a wide array of textual media forms, Thoburn invites us to challenge the commodity form of books-to stop imagining books as transcendent intellectual, moral, and aesthetic goods unsullied by commerce. His critique is, instead, one immersed in the many materialities of text. Anti-Book engages with an array of writing and publishing projects, including Antonin Artaud's paper gris-gris, Valerie Solanas's SCUM Manifesto, Guy Debord's sandpaper-bound Mémoires, the collective novelist Wu Ming, and the digital/print hybrid of Mute magazine. Empirically grounded, it is also a major achievement in expressing a political philosophy of writing and publishing, where the materiality of text is interlaced with conceptual production. Each chapter investigates a different form of textual media in concert with a particular concept: the small-press pamphlet as "communist object," the magazine as "diagrammatic publishing," political books in the modes of "root" and "rhizome," the "multiple single" of anonymous authorship, and myth as "unidentified narrative object." An absorbingly written contribution to contemporary media theory in all its manifestations, Anti-Book will enrich current debates about radical publishing, artists' books and other new genre and media forms in alternative media, art publishing, media studies, cultural studies, critical theory, and social and political theory.